The Effectiveness of Baby Massage on the Quality of Sleep of Babies Aged 0-6 Months - Grace Carol Sipasulta; Lamria Situmeang; Ayunin syahida (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Poor sleep quality in infants can affect their physical and emotional growth and development. One intervention that is believed to improve the quality of baby sleep is baby massage. However, the effectiveness of infant massage in improving the quality of sleep of infants aged 0-6 months still needs to be studied more deeply, given the limitations of research in Indonesia related to this. Purpose: this study aims to test the effectiveness of infant massage on the quality of sleep of infants aged 0-6 months in the working area of Ambacang Health Center, Padang.  Method: the design of this study is a quasi-experimental pretest-posttest approach. The sample consisted of 15 infants who met the inclusion criteria, who were given an infant massage intervention for 7 consecutive days. Sleep quality measurements were performed before and after the intervention using the infant sleep quality questionnaire. The Data were analyzed by univariate and bivariate analysis, as well as paired T-tests to see significant differences. Result: the results of the univariate analysis showed an increase in sleep quality score from an average of 12.4 (before) to 19.3 (after). The paired T-test showed a significant difference between the quality of the baby's sleep before and after the baby massage (p = 0.002), which indicates the effectiveness of the baby massage in improving the quality of the baby's sleep. Implications: infant massage can be used as a non-pharmacological method to improve infant sleep and can be applied in health centers. Conclusion: baby massage effectively improves sleep quality of babies aged 0-6 months, supporting optimal baby development.